2015
DOI: 10.1158/2326-6066.cir-14-0148
|View full text |Cite
|
Sign up to set email alerts
|

CARD9 Promotes Sex-Biased Colon Tumors in the APCmin Mouse Model

Abstract: Caspase recuitment domain-containing protein 9 (CARD9) functions in different inflammation pathways to elicit responses to microbial signals and is known to affect intestinal inflammation. Examining the APC min mouse model of intestinal tumorigenesis and using stringently controlled, sex-and age-matched pairs of CARD9-competent and CARD9-deficient mice, we have found that CARD9 has a restricted but strong effect on tumorigenesis in the large intestine. We have found that CARD9 reduces viability specifically in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…find an ectopic overexpression of CARD9 in gastric B‐cell lymphoma. Leo et al . demonstrate that CARD9 promotes sex‐biased colon tumors in the adenomatous polyposis coli multiple intestinal neoplasia (APC min ) mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…find an ectopic overexpression of CARD9 in gastric B‐cell lymphoma. Leo et al . demonstrate that CARD9 promotes sex‐biased colon tumors in the adenomatous polyposis coli multiple intestinal neoplasia (APC min ) mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura et al 4 find an ectopic overexpression of CARD9 in gastric B-cell lymphoma. Leo et al 30 demonstrate that CARD9 promotes sex-biased colon tumors in the adenomatous polyposis coli multiple intestinal neoplasia (APC min ) mouse model. Our recently study on colitis-associated colon cancer confirms a critical role of CARD9 in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…That being said, a diminished hematocrit and an increased spleen as well as liver weight are expected outcomes in Apc Min mice fed a high‐fat diet . There are a few studies describing gender‐dependent effects on adenoma development in mice carrying a mutation in the APC gene, which are, for example, related to factors such as physical exercise or genotype . Nevertheless, the specific reason for the observation that Vineatrol®30 is more effective in male animals remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of CARD9 mRNA in gastric B-cell lymphoma [6] indicated that CARD9 was related with tumorigenesis and development. CARD9 can promote tumorigenesis of large intestines in the male APC min mice, which mimics the genetic lesions associated with human familial adenomatous polyposis [7]. In addition, upregulation of CARD9 was also found in renal cell carcinoma and was significantly associated with poor prognosis [8].…”
Section: Introductionmentioning
confidence: 90%